Multipurpose Agricultural Robot Platform. Issue 1 (July 2020) - Thaitanun, Sunti; Loetthanaphan, Sitthivich; Wanichanan, Sangdad; Myint, Ye Moe; Phanomchoeng, Gridsada; Chancharoen, Ratchatin; Wuttisittikulkij, Lunchakorn; Saadi, Muhammad; Wijayasekara, Sanika K.
Abstract: During the last decade, agricultural sector has witnessed a wide adoption of cutting edge technology not only to improve the quality and quantity of the crops but also to ease the labour burden. These technological oriented and innovative agricultural solutions have opened new horizons for opportunists, researchers and investors along with the creation and development of new markets. Robotic and automation technologies are now complementing farmers in various ways. In this paper, we present the mechanical and electrical design of multi-purpose agricultural robot which has the capabilities to move in three Cartesian coordinate axis along with the functionality of harvesting small sized fruits with the help of grippers. Our developed robot prototype can be controlled via remote control. Prototype testing results show that the developed robot can reach to the target by passing any small sized obstacle and harvest the fruit. We believe that such low cost, less complex and indigenously developed multipurpose agricultural robots can help farmers by reducing their labour cost and human effort.